Study on the Optimal Harvest Time of Stems and Leaves of Astragalus membranaceus Based on HPLC and Chemometrics - Xiaolan LI; Xinyuan GAO; Jie SUN; Henan WEI; Lili GUO (Shipin gongye ke-ji, 2024)
Objective: To establish the HPLC method for simultaneous content determination of seven flavonoids and three saponins ingredients in the stems and leaves of Astragalus membranaceus, and to investigate its dynamic variation rules in different harvest time so as to determine the appropriate harvest time. Methods: After conducting the methodological investigation of chromatographic conditions, the HPLC detection method of ten active components was established. Then the method was used to determine the content of ten active components in the stems and leaves of Astragalus membranaceus in different harvest time. Finally, the cluster analysis, principal component analysis and entropy weight TOPSIS method were used to analyze the dynamic variation and distribution of the above components. Results: There were significant differences in the contents of the ten ingredients in the aerial parts of Astragalus membranaceus during different harvest periods (P<0.05). The total content of flavonoids in stems was higher from late August to September, and that of saponins was reached in early August. In contrast, the highest total amount of flavonoids in leaves was shown in the period of August to early September, and the amount of total saponins was not obviously changed. The results of chemometrics analysis showed that the contents of chemical components in the stems and leaves of Astragalus membranaceus before August were significantly different with that after August. Further entropy weight TOPSIS analysis showed that the stems of Astragalus membranaceus from August to September shared better comprehensive quality than other periods, and the leaves of Astragalus membranaceus in August presented the best quality, suggesting that the stems and leaves of Astragalus membranaceus should be harvested in late August. Conclusion: The HPLC method could be used for the simultaneous content detection of flavonoids and saponins ingredients in the aerial parts of Astragalus membranaceus. The suggested harvest period of the stems and leaves of Astragalus membranaceus could provide scientific basis for the quality control and further utilization of the stems and leaves of Astragalus membranaceus.